2021
DOI: 10.2147/rru.s323823
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors for MRI-Invisible Prostate Cancer in Patients Undergoing Transperineal Saturation Biopsy

Abstract: Purpose Prostatic multi-parametric magnetic resonance imaging (mpMRI) has markedly improved the assessment of men with suspected prostate cancer (PCa). Nevertheless, as mpMRI exhibits a high negative predictive value, a negative MRI may represent a diagnostic dilemma. The aim of this study was to evaluate the incidence of positive transperineal saturation biopsy in men who have negative mpMRI and to analyse the factors associated with positive biopsy in this scenario. Patients and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Medina et al [ 21 ] highlighted a concern of 5ARI use being associated with MRI invisible prostate cancer. However, the study did not make a distinction between clinically significant and insignificant prostate cancer, and 65% of the prostate cancers detected yielded Gleason 3 + 3 histology.…”
Section: Discussionmentioning
confidence: 99%
“…Medina et al [ 21 ] highlighted a concern of 5ARI use being associated with MRI invisible prostate cancer. However, the study did not make a distinction between clinically significant and insignificant prostate cancer, and 65% of the prostate cancers detected yielded Gleason 3 + 3 histology.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the PI-RADS v.2.0 exhibited good accuracy in predicting csPCa [22]. In 2021, Artiles et al concluded that 5-ARI exposure was an independent predictor of csPCa after analyzing 34 men suspected of having PCa with negative mpMRI results who underwent saturation biopsies [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a large prostate volume, one of the predictive factors of TB negativity, predicted greater biopsy needle tip deflection, thus affecting biopsy accuracy (21). Moreover, a large prostate volume significantly predicts the absence of CSPC on SB (22). Also, Phelps et al showed that patients who had a large prostate volume (p=0.016) were at increased risk of harboring CSPC that would be missed by TB but detected by SB (11).…”
Section: Discussionmentioning
confidence: 99%